CORRUPTION IN ACESSING AND UTILIZING THE COMMON PROPERTY RESOURCES IN INDONESIA - Lengga Pradipta (Research Centre for Population, Indonesian Institute of Sciences, 2016)
This article reviews some corruption cases that are associated with natural resources management, especially in accessing and utilizing common property resources in Indonesia. It attempts to extract lessons from regulations and actions that have emerged in all levels and across many sectors. This article develops social-ecological systems (SES) framework to deliver a clear roadmap for incorporating more ecological or natural characteristics into studies that explores linkage social and legal systems. The framework therefore considers how problems are deï¬ned and how action and policy are formulated to deal with these problems. This article provides an in-depth investigation in Pasaman district. The data is gathered by interviewing local people who live around palm plantations in West Pasaman. Corruption in the context of managing common property resources brings many disadvantages to community and State because it will lead to the scarcity of resources. Overall, eradicating corruption is not only on the hands of community or private sectors, but also needs active involvement from government and policy-makers as the main stakeholders.